MARHAENISME : TELAAH PEMIKIRAN SUKARNO TAHUN 1927-1933 - Cici Eliya Melawati; Kuswono Kuswono (Swarnadwipa, 2018)
Many understandings that were born in the period of the movement, including the Marhaenism which was triggered by Sukarno. Marhaenism was born from Sukarno's awareness of the fate of the Indonesian people and people who are constantly impoverished and suffering by the practice of Colonialism This made Sukarno aware of his desire to be independent and determine the destiny of the country WITHOUT foreign interference. Marhaenism became an ideology in fighting for the fate of the oppressed Indonesian people. Marhaenism became the foundation of the PNI's struggle which was founded in 1927. PNI was a tool to defend the colonized Indonesian people. The desired concept of independence is economic, social and political independence that can be felt by all Indonesians. The hallmark of Marhaenism is the Socio-Nationalist principle, Socio-Democracy which describes the spirit and principles of the Marhaen who want independence. We can feel this Marhaenism influence in every mass oration made by Sukarno. Where Sukarno always gathered masses in large numbers and shouted Marhaen as the ideology of the oppressed Indonesian people. Prior to the establishment of the PNI, Sukarno first established an association named Studie Club, which became the forerunner of the establishment of PNI which was continued by Partindo to continue the spirit of Marhaenism.